Design, synthesis, and insecticidal activity evaluation of piperine derivatives - Zhang, Chiying; Tian, Qingqiang; Li, Yahui (Frontiers in Chemistry, 2022)
Molecular design and structural optimization of natural products has been one of the most effective ways to innovate pesticides to achieve integrated management of agricultural pests. Here, a series of piperine bisamide compounds were designed and synthesized as control agent for P. xylostella. The in vivo activity assay showed that all compounds displayed a better insecticidal activity than the lead compound piperine toward P. xylostella at 200 mg/L. And compound D28 displayed a moderate insecticidal activity with 43% and 23% mortality activity (48 h) to P. xylostella at 200 mg/L and 50 mg/L independently. The work provides a new method for design of more effective and environmentally friendly pesticides using the piperine as lead compound, and linear bisamide could also be an active substructure for developing new insecticides.